Trends of polyphenolics and anthocyanins accumulation along ripening stages of wild edible fruits of Indian Himalayan region - Belwal, Tarun (Sci Rep, 2019)
Wild fruits are important food resources that provide health promoting nutraceutical components, which vary with ripening stages. In present study, five wild edible fruits of Indian Himalayan Region i.e., Myrica esculenta, Berberis asiatica, Rubus ellipticus, Pyracantha crenulata and Morus alba were examined for their nutraceutical potential at different ripening stages. The results of present study showed that polyphenolic concentration decreased whereas anthocyanin level increased with fruit ripening, however few species and compounds showed different trends. Among the tested fruit species, unripe fruits of B. asiatica followed by M. esculenta were found to be the best for harvesting polyphenolics (especially catechin), while ripen fruits of M. esculenta followed by B. asiatica were found the best for anthocyanin (cyanin and delphinidin) extraction. The results from this study can be effectively used by the harvesters, consumers, traders and food and nutraceutical industries to harness maximum nutraceutical potential depending on the preferred compounds and ripening stages of these species.